Gut microbiota in patients with Parkinson's disease in southern China. (August 2018) - Lin, Aiqun; Zheng, Wenxia; He, Yan; Tang, Wenli; Wei, Xiaobo; He, Rongni; Huang, Wei; Su, Yuying; Huang, Yaowei; Zhou, Hongwei; Xie, Huifang
Abstract: Introduction: Accumulating evidence has revealed alterations in the communication between the gut and brain in patients with Parkinson's disease (PD), and previous studies have confirmed that alterations in the gut microbiome play an important role in the pathogenesis of numerous diseases, including PD. The aim of this study was to determine whether the faecal microbiome of PD patients in southern China differs from that of control subjects and whether the gut microbiome composition alters among different PD motor phenotypes. Methods: We compared the gut microbiota composition of 75 patients with PD and 45 age-matched controls using 16S rRNA next-generation-sequencing. Results: We observed significant increases in the abundance of four bacterial families and significant decreases in the abundance of seventeen bacterial families in patients with PD compared to those of the controls. In particular, the abundance of Lachnospiraceae was reduced by 42.9% in patients with PD, whereas Bifidobacteriaceae was enriched in patients with PD. We did not identify a significant difference in the overall microbial composition among different PD motor phenotypes, but we identified the association between specific taxas and different PD motor phenotypes. Conclusions: PD is accompanied by alterations in the abundance of specific gut microbes. The abundance of certain gut microbes was altered depending on clinical motor phenotypes. Based on our findings, the gut microbiome may be a potential PD biomarker. Highlights: We found altered gut microbiota composition in patients with PD in southern China. We found the association between specific taxas and different PD motor phenotypes. The abundance of Lachnospiraceae was reduced by 42.9% in patients with PD.